Molecular Characterization of Staphylococcus sciuri Strains Isolated from Humans - Couto, Isabel (American Society for Microbiology, 2000)
We previously characterized over 100 Staphylococcus sciuri isolates, mainly of animal origin, and found that they all carried a genetic element (S. sciuri mecA) closely related to the mecA gene of methicillin-resistant Staphylococcus aureus (MRSA) strains. We also found a few isolates that carried a second copy of the gene, identical to MRSA mecA. In this work, we analyzed a collection of 28 S. sciuri strains isolated from both healthy and hospitalized individuals. This was a relatively heterogeneous group, as inferred from the different sources, places, and dates of isolation and as confirmed by pulsed-field gel electrophoresis analysis. All strains carried the S. sciuri mecA copy, sustaining our previous proposal that this element belongs to the genetic background of S. sciuri. Moreover, 46% of the strains also carried the MRSA mecA copy. Only these strains showed significant levels of resistance to beta-lactams. Strikingly, the majority of the strains carrying the additional MRSA mecA copy were obtained from healthy individuals in an antibiotic-free environment. Most of the 28 strains were resistant to penicillin, intermediately resistant to clindamycin, and susceptible to tetracycline, erythromycin, and gentamicin. Resistance to these last three antibiotics was found in some strains only. The findings reported in this work confirmed the role of S. sciuri in the evolution of the mechanism of resistance to methicillin in staphylococci and suggested that this species (like the pathogenic staphylococci) may accumulate resistance markers for several classes of antibiotics.